Conditioning solid tumor microenvironment through inflammatory chemokines and S100 family proteins. Issue 1 (28th August 2015) - Nasser, Mohd W.; Elbaz, Mohamad; Ahirwar, Dinesh K.; Ganju, Ramesh K.
Highlights: Chemokines/S100 proteins produced from either tumor or stromal cells modulate tumor microenvironment (TME). Chemokines/S100 proteins, depending on their category, have tumor promoting or regressing properties. Chemokine-based therapy should be modulated for successful clinical trials. New strategies have been developed to study the TME which may help eventually in assessment of TME-based therapies. Abstract: Recently, there has been growing attention to the role of the tumor microenvironment (TME) in cancer growth, metastasis and emergence of chemotherapy resistance. Stromal and tumor cells make up the TME and interact with each other through a complex cross-talk manner. This interaction is facilitated by a variety of growth factors, cytokines, chemokines and S100 proteins. In this review, we focus on chemokines and their cognate receptors in regulating the tumorigenic process. Chemokines are cytokines that have chemotactic potential. Chemokine receptors are expressed on tumor cells and stromal cells. Chemokines and their cognate receptors modulate tumor growth and metastasis in a paracrine and autocrine manner. They play a major role in the modulation of stromal cell recruitment, angiogenic potential, cancer cell proliferation, survival, adhesion, invasion and metastasis to distant sites. In addition, a new class of calcium binding family S100 proteins has been getting attention as they play significant roles in tumor progression and metastasis by modulating TME. Here, we highlight recent developments regarding the inflammatory chemokine/S100 protein systems in the TME. We also focus on how chemokines/S100 proteins, through their role in the TME, modulate cancer cell ability to grow, proliferate, invade and metastasize to different organs. This review highlights the possibility of using the chemokine/chemokine receptor axis as a promising strategy in cancer therapy, the current difficulties in achieving this goal, and how it could be overcome for successful future therapeutic intervention.